Aesthetic Total Reconstruction of Lower Eyelid Using Scapha Cartilage Graft on a Vascularized Propeller Flap - Uemura, Tetsuji (Plast Reconstr Surg Glob Open, 2016)
BACKGROUND: The aim of this study was to review the results of a cohort of patients based on our experience with a new technique for total lower eyelid reconstruction after a large defect caused by malignant tumor and trauma. A scapha cartilage graft with small skin on a vascularized propeller flap was used for 16 cases requiring lower eyelid reconstruction. METHODS: Patients were identified from a database, and a retrospective case note review was conducted. The scapha cartilage graft was sutured to the margin of the defect of the palpebral conjunctiva and tarsus. The propeller flap, rotated by a perforator-based lateral orbital flap or a subcutaneous-based nasolabial flap, was vascularized on the scapha cartilage graft as anterior lining of the lower eyelid. The follow-up, including results of slit-lamp examination, lasted for varying periods, but often it was for 12 months. RESULTS: The scapha cartilage graft with small skin on a vascularized propeller flap was viable in all cases. Slit-lamp examination detected no irritation or injury of the conjunctiva and cornea, and visual acuity was maintained in all cases. A deformity in the donor helix by this technique was also improved by getting a smaller skin harvested from the scapha. CONCLUSION: Use of the scapha cartilage graft with small skin on a vascularized propeller flap allows for a good fit to the orbit, short operative time under local anesthesia, good graft viability, and a good esthetic result with minimal donor site morbidity.